Low-Dimension Nanomaterial-Based Sensing Matrices for Antibiotics Detection: A Mini Review - Dong, Yucan; Li, Fengting; Wang, Ying (Frontiers in Chemistry, 2020)
Antibiotics is a kind of secondary metabolite with anti-pathogen effect or other qualities, produced by microorganism (including bacterium, fungi and actinomyces) or higher animals and plants in their life course. It is a kind of chemical that can disturb the developmental functions of other living cells. It is impossible to avoid its pervasion into all kinds of environmental media via all kinds of methods, and being a trigger for environmental risks correspondingly. As described above, antibiotics are presently deemed as a new type of pollution, with its content in the media (for example, water or food) becoming a focus. Due to its special qualities, nanomaterials, as the most promising sensing material, can be used to produce sensors with extraordinary detecting performance and good stability which can be applied to detection in complicated materials. As for low-dimension nanomaterials, its quantum size effect and dielectric confinement effect are more remarkable. Thus it is applied more in detection of antibiotics. This article focus on the role that low-dimension nanomaterials plays in antibiotics detection, summarizes the application of low-dimension nanomaterials in antibiotics detection and the theorem of sensors in all kinds of antibiotics detection, mentions the approaches to optimize sensors’ sensitivity, such as mixture and modification, and also discusses the trend of the application of low-dimension nanomaterials in antibiotics detection.